Syringin inhibits endogenous volume regulated anion channel currents of HEK293 cells in hypotonic circumstances - Ziwei Xu; Wei Yao; Minyan Liang; Song Wang; Longhui Lu; Jingjing Wang; Na Zhu; Liping Huang (Wiley, 2023)
Abstract Syringin is a natural chemical compound first isolated from the bark of lilac and is known to have neuroprotective effects in middle cerebral artery occlusion (MCAO). Volume regulated anion channel (VRAC) is a cell swelling‐activated anion channel, which is implicated in brain ischemia. However, the mechanism underlying the syringin protecting the neuron from damage in MCAO is still unclear. We hypothesized that syringin has an inhibitory effect on the opening of VRAC channels. To access the effect of syringin on VRAC currents and predict how syringin interacts with VRAC proteins, we performed whole‐cell patch‐clamp experiments using HEK293 cells. Initially, HEK293 cells were perfused with isotonic extracellular solution, followed by hypotonic extracellular solution to stimulate endogenous VRAC currents. Once the VRAC currents reached a steady state, the hypotonic solution containing syringin was perfused to study the effect of syringin on VRAC currents. The potential interaction between syringin and the VRAC protein was investigated using molecular docking as a predictive model. In this study, we found that syringin moderately inhibited VRAC currents in a dose‐dependent manner. The potential binding of syringin to LRRC8 protein was predicted through in silico molecular docking, which suggests an affinity of −6.6 kcal/mol and potential binding sites of arginine 103 and leucine 101. Our results herein characterize syringin as an inhibitor of the VRAC channels, which provides valuable insights for the future development of VRAC channel inhibitors.